Comparing the effects of balance training with and without cognitive tasks on the quality of life and balance performance in community-dwelling older adults: a single-blind randomized clinical trial - Ehsan Sinaei; Fahimeh Kamali; Ahmadreza Nematollahi; Zahra Etminan (Shiraz University of Medical Sciences, 2016)
Background: Aging process can deteriorate the ability to maintain balance, specifically under dual-task conditions. Thus far, different methods of exercises therapy have been applied to improve balance performance of older adults. The present study was designed to compare the effects of two protocols of balance training on the quality of life (QoL) and balance performance in older adults with mild balance impairments. Methods: Twenty-four older adults over 60 years old were allocated randomly into single-task (n=12) and dual-task (n=12) exercise groups. Single-task group received routine balance exercises, over a four-week period and dual-task group was treated by the same exercise program plus a cognitive task. QoL and balance status were assessed by the Short-Form Health Survey (SF-36) and Fullerton Advanced Balance scale (FAB) questionnaires, before and after the interventions. Results: After four weeks of training, balance performance and some factors of QoL improved significantly in both groups (P<0.05). However, there were no significant differences in any of the variables between the two groups. Conclusion: Balance exercises, under both single- and dual-task conditions can improve the balance level and some aspects of QoL in older adults with mild balance impairments, with no priority of one group over another.